Articuler la politique Trame verte et bleue et la séquence Éviter-réduire-compenser : complémentarités et limites pour une préservation efficace de la biodiversité en France - Julie Chaurand; Charlotte Bigard; Sylvie Vanpeene-Bruhier; John D. Thompson (VertigO)
Biodiversity conservation is more than ever an imperative for urban and territorial planning. In this regard, French public policies such as the Green and Blue Infrastructure (TVB) and the mitigation hierarchy (ERC) are regulatory tools dealing with sustainable urban planning and the preservation of biodiversity beyond protected areas. These two public policies have been explicitly brought to the fore in several laws and are now part of the planning procedure and important elements in discussion with territorial stakeholders. However, they encounter difficulties with regard their implementation in urban planning documents and thus to provide a means to contribute to stopping the loss of biodiversity. In this article we describe and compare the historical trajectories of these two public policies in France. Then we present the pitfalls concerning their integration within the framework of strategic urban and territorial planning. In order to overcome these difficulties, we identify different sources of potential complementarity between the two policies and we examine the main limits these articulations imply. Finally, we question the inter-territorial coherence of their implementation in light of the notion of "ecological solidarity" that has recently been introduced into legislation for biodiversity conservation as a basic principle to guide public decision-making.